PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA PADA KONSEP TEKANAN - ERI HARTATI (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2022)
This classroom action research is entitled Application of Problem Based Learning (PBL) Models to Improve Students' Science Learning Outcomes on the Concept of Pressure. This learning model is a problem-based learning model where students are invited to be able to solve problems in learning. The stages of this model have 5 stages of learning, namely: orientation of students to problems, organizing students to learn, guiding individual/group experiences, developing and presenting work, analyzing and evaluating the problem solving process. Based on the results of data analysis, it was obtained data that student learning outcomes increased the average score from 68.75 in cycle 1 to 81.25 in cycle 2 and the presentation of learning completeness increased and exceeded the level of classical learning completeness, namely 87.5%. Observations of learning carried out by observers also the understanding and activities of students in learning have improved very well. With these results, it is hoped that this learning model can be used as reference material for learning models in the classroom. ABSTRAKPenelitian tindakan kelas ini berjudul Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar IPA Siswa Pada Konsep Tekanan . Model pembelajaran ini merupakan model pembelajaran yang berbasis masalah dimana siswa diajak untuk dapat memecahkan masalah dalam pembelajaran. Adapun tahapan dari model ini memiliki 5 tahapan pembelajaran, yaitu : orientasi peserta didik pada masalah, mengorganisasi peserta didik untuk belajar, membimbing pengalaman individual/kelompok, Mengembangkan dan menyajikan hasil karya, menganalisis dan mengevaluasi proses pemecahan masalah. Berdasarkan hasil analisis data diperoleh data bahwa hasil belajar siswa terjadi peningkatan nilai rata-rata dari 68,75 pada siklus 1 menjadi 81,25 pada siklus 2 dan presentasi ketuntasan belajarpun mengalami peningkatan dan melebihi tingkat ketuntasan belajar klasikal yaitu 87,5 %. Observasi pembelajaran yang dilakukan oleh observerpun pemahaman dan aktivitas siswa dalam pembelajaran mengalami peningkatan yang sangat baik. Dengan hasil tersebut diharapkan model pembelajaran ini bisa di pakai sebagai bahan reverensi model pembelajaran di dalam kelas.